Gluing powder for cemented filling of sulfur-containing tailings and preparation method thereof
By using glue-fixed powder composed of slag powder, silicon fume, desulfurization gypsum and cement clinker, and using exciters and modifiers to regulate the mineral crystal development process, the expansion and cracking problems caused by the solidification of sulfur-containing tailings of traditional cement are solved, the strength and stability of the filling body are improved, and the ecological environment is protected.
Patent Information
- Application Number
- CN202411691712.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-14
AI Technical Summary
When traditional silicate cement is used to cure sulfur-containing tailings, it will cause expansion and cracking of the filler, and under acidic conditions, it will promote the release of heavy metal elements and damage the ecological environment.
It is provided with a glue-fired powder for sulfur-containing tailings, which consists of slag powder, silicon fume, desulfurization gypsum and cement clinker. Through the joint action of an exciter and a modifier, the mineral crystal development process is adjusted, the pore size structure of the filling cured body is improved, and the strength and curing stability of the cemented filling body are improved.
By optimizing the pore size structure of the filler and the morphology of the mineral crystal, the crystal growth stress is reduced, the compressive strength and curing stability of the filler are improved, the risk of heavy metal release under acidic conditions is reduced, and the ecological environment is protected.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of underground mine filling, and particularly relates to a cementing powder used for cementing filling of sulfur-containing tailings and a preparation method thereof. Background Art
[0002] A large amount of solid waste will be generated in the process of mining and utilization of mineral resources, especially the bulk tailings and metallurgical slag generated in the process of mineral processing and smelting. If not handled properly, it will not only occupy land and pollute the environment, but also cause safety problems. With my country's increasing attention to and strict management of environmental protection in resource development and the introduction of a series of environmental protection laws, solid waste emissions are restricted or reduced. In recent years, not only has the legislation system imposed high stacking and processing fees and increased penalties for waste emissions, but also "waste-based production" has been implemented to limit the emission of solid waste from the source and achieve environmental protection. Therefore, the treatment and utilization of solid waste generated in the process of mineral resource development is an important issue facing the green and sustainable development of mines.
[0003] Cemented paste backfill is considered to be one of the best methods for tailings management and green mining. It refers to mixing binder, filling aggregate and water in a specific proportion, and then sending them to the goaf by gravity or pumping until they solidify. The advantages of this method in terms of environmental protection and economic benefits are becoming more and more significant. On the one hand, cemented paste backfill makes efficient use of mine dressing and smelting waste (such as tailings, waste rock and metallurgical slag, etc.), thereby reducing the impact of mining development on the ecological environment; on the other hand, it can refill the underground voids caused by mining ore, thereby reducing the risk of surface subsidence and supporting nearby rocks, improving resource recovery rate. Cement is widely used as a cementitious material for cemented backfilling. After hardening, it provides strength for the cemented tailings backfill body, but the cost of cement accounts for about 70% of the total filling cost, which has become one of the main factors limiting the application of this method. At the same time, the large amount of carbon dioxide emissions (about 0.9 tons of CO2 are emitted for every ton of backfill slurry produced), the large-scale use of cement will undoubtedly cause a serious burden on the ecological environment. The research on low-cost, high-performance and environmentally friendly cementitious materials has become an important topic for cemented paste backfilling.
[0004] Metal ores are usually rich in sulfide minerals, which makes the tailings contain a large amount of sulfur, which reacts with oxygen and water to form sulfate and produce a large amount of hydrogen ions. If traditional silicate cement is used to solidify sulfur-containing tailings, expansion products such as calcium sulfonate will be produced, causing the filling body to expand and crack, and the strength of the filling body will deteriorate. And due to the production of acid, the cement hydration product CSH gel will also decalcify, further reducing the mechanical properties of the solidified body. In addition, acidic conditions will promote the release of heavy metal elements in the tailings, forming acidic mine drainage and damaging the local ecological environment. Summary of the invention
[0005] The present invention provides a cementing powder for sulfur-containing tailings and a preparation method thereof to replace cement clinker used for underground mine filling. Through the combined action of an activator and a modifier on metallurgical slag, the dissolution and dispersion of various components in the early stage are promoted, the mineral crystal development process is regulated, the pore structure of the filling solid body is improved, and the strength and curing stability of the cemented filling body are improved.
[0006] The present invention achieves the above-mentioned effects through the following technical solutions and means.
[0007] An embodiment of the present invention provides a cement powder for sulfur-containing tailings, characterized in that the cement powder is composed of a base material and auxiliary materials, and the cement powder base material includes the following raw material components in mass percentage: 60-90wt% of slag powder, 1-5wt% of silica fume, and 35-9wt% of active stimulant, and the sum of the percentages of each raw material is 100%.
[0008] Preferably, the cementing powder for sulfur-containing tailings is characterized in that the specific surface area of the slag powder is ≥400m 2 / kg, the activity index at 7 days and 28 days was ≥70% and 95% respectively, and the Al2O3 content was >11%.
[0009] Preferably, the cementing powder for sulfur-containing tailings is characterized in that the active activator raw material components are desulfurized gypsum and ordinary Portland cement clinker, and the mass ratio thereof is 1-20:5-40.
[0010] Preferably, the cementing powder for sulfur-containing tailings is characterized in that the attached water content and chloride ion content of the desulfurized gypsum are ≤12% and 300 mg / kg respectively, and the content of calcium sulfate dihydrate (CaSO4·2H2O) is ≥90%.
[0011] Preferably, the cement powder for sulfur-containing tailings is characterized in that the specific surface area of the cement clinker is ≥300m 2 / kg, 28d flexural and compressive strength ≥6.5MPa and 42.5MPa respectively;
[0012] Preferably, the cement powder for sulfur-containing tailings is characterized in that the cement powder auxiliary materials account for 0.5-3wt% of the total mass percentage of the cement powder, including a solvent promoter, an early strength agent, and a pore regulator; further, the ratio of each raw material is as follows: solvent promoter: early strength agent: pore regulator is 20-40: 20-40: 20-60.
[0013] Preferably, the cementing powder for sulfur-containing tailings is characterized in that the dissolution agent is a compound of one or more of sodium carbonate, calcium chloride, and calcium nitrate; the early strength agent is a compound of one or more of sodium fluorosilicate, sodium sulfate, and potassium aluminum sulfate; and the pore regulator is a compound of one or more of fatty alcohol polyoxyethylene ether, tributyl phosphate, and polyether silicone.
[0014] Preferably, the cementing powder for sulfur-containing tailings is characterized in that the sulfur content in the chemical composition of the sulfur-containing tailings is 5-15%, and the sulfur element mainly exists in the form of pyrite (FeS2).
[0015] Preferably, the method for preparing a cement powder for sulfur-containing tailings is characterized by:
[0016] (1) weighing slag powder, silica fume, desulfurized gypsum and cement clinker according to a certain mass ratio, mixing, stirring and grinding to obtain a sulfur-containing tailings glue solid powder base material;
[0017] (2) mixing, grinding and stirring the solvent promoter, early strength agent and pore regulator in the modifier in a certain mass ratio to obtain a sulfur-containing tailings glue solid powder auxiliary material;
[0018] (3) The cement powder base material in (1) and the cement powder auxiliary material in (2) are mixed evenly to obtain the cement powder for sulfur-containing tailings.
[0019] The beneficial effects of the present invention are:
[0020] Through the combined action of the activator and the early strength agent, the appropriate ion concentration and alkalinity in the filling system are regulated and maintained, the mineral crystal development process during the hydration process of the cementitious material is adjusted, and the morphology of the ettringite crystals is optimized, so that the ettringite mainly plays the role of filling the voids, reducing the crystal growth stress and creating conditions for the strength development of the filling.
[0021] By improving the pore size distribution and pore-throat ratio of the filling solid body, the pores inside the filling body are reduced and relatively independent, the oxygen and water mass transfer process in the filling body is changed, the reactivity of oxygen and water inside the filling body is reduced, and the solidification performance of the cementitious material on sulfur tailings is improved. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] (1) 1.00 kg of sulfur-containing tailings cement powder is prepared according to the following mass ratio, wherein the cement powder is composed of a base material and auxiliary materials, wherein the mass percentage of the auxiliary materials in the cement powder is 1 wt%; the base material components of the cement powder are, by mass percentage, 77 wt% of slag powder, 3 wt% of silica fume, and 20 wt% of an active activator; the active activator comprises silicate cement and desulfurized gypsum, wherein the mass ratio is 3:2
[0025] (2) The auxiliary materials include a solubilizing agent, an early strength agent, and a pore regulator, and the mass ratio thereof is 1:1:1; wherein the solubilizing agent is composed of sodium carbonate and calcium chloride, and the ratio of the two is 1:2; the early strength agent is a mixture of sodium fluorosilicate and potassium aluminum sulfate, and the ratio of the two is 1:1; the pore regulator is composed of fatty alcohol polyoxyethylene ether and tributyl phosphate, and the ratio of the two is 2:3;
[0026] (3) weighing the auxiliary material and the cement powder base material prepared in (1) according to a mass ratio of base material to auxiliary material of 99:1, and dry mixing and stirring, and after mixing evenly, a cement powder for cementing and filling of sulfur-containing tailings can be obtained;
[0027] (4) Weighing 0.926 kg of the cement powder prepared in (3) above and mixing it with 7.935 kg of sulfur-containing tailings mortar with a mass concentration of 70%, wherein the mass of the sulfur-containing tailings curing agent accounts for 14.3% of the dry weight of the sand in the sulfur-containing tailings mortar, that is, the cement-sand ratio is 1:6, adding 0.140 kg of water to adjust the mass concentration of the mixed slurry to 72%, and stirring evenly to obtain a sulfur-containing tailings cementitious filling material;
[0028] (5) The sulfur-containing tailings cementing filling material prepared in (4) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009).
[0029] Example 2
[0030] (1) 1.00 kg of sulfur-containing tailings cement powder is prepared according to the following mass ratio, wherein the cement powder is composed of a base material and auxiliary materials, wherein the mass percentage of the auxiliary materials in the cement powder is 1 wt%; the base material components of the cement powder are calculated by mass percentage, including: 77 wt% of slag powder, 3 wt% of silica fume, and 20 wt% of an active activator; the active activator includes silicate cement and desulfurized gypsum, wherein the mass ratio is 3:2;
[0031] (2) The auxiliary materials include a solubilizing agent, an early strength agent, and a pore regulator, and the mass ratio thereof is 1:1:2; wherein the solubilizing agent is composed of sodium carbonate and calcium chloride, and the ratio of the two is 2:1; the early strength agent is a mixture of sodium fluorosilicate and potassium aluminum sulfate, and the ratio of the two is 3:2; the pore regulator is composed of fatty alcohol polyoxyethylene ether and tributyl phosphate, and the ratio of the two is 1:2;
[0032] (3) weighing the modifier and the cement powder base material prepared in (1) according to a mass ratio of base material to modifier of 99:1, and dry mixing and stirring, and after mixing evenly, a cement powder for sulfur-containing tailings can be obtained;
[0033] (4) Weighing 0.900 kg of the cement powder prepared in (3) above and mixing it with 7.714 kg of sulfur-containing tailings mortar with a mass concentration of 70%, wherein the mass of the sulfur-containing tailings curing agent accounts for 14.3% of the dry weight of the sand in the sulfur-containing tailings mortar, that is, the cement-sand ratio is 1:6, adding 0.386 kg of water to adjust the mass concentration of the mixed slurry to 70%, and stirring evenly to obtain a sulfur-containing tailings cementitious filling material;
[0034] (5) The sulfur-containing tailings cementing filling material prepared in (4) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009).
[0035] Example 3
[0036] (1) 1.00 kg of sulfur-containing tailings cement powder is prepared according to the following mass ratio, wherein the cement powder is composed of a base material and auxiliary materials, wherein the mass percentage of the auxiliary materials in the cement powder is 1 wt%; the base material components of the cement powder are calculated by mass percentage, including: 77 wt% of slag powder, 3 wt% of silica fume, and 20 wt% of an active activator; the active activator includes silicate cement and desulfurized gypsum, wherein the mass ratio is 3:2;
[0037] (2) The auxiliary materials include a solubilizing agent, an early strength agent, and a pore regulating agent, and the mass ratio thereof is 1:1:1; wherein the solubilizing agent is composed of sodium carbonate and calcium nitrate, and the ratio of the two is 1:1; the early strength agent is a mixture of sodium fluorosilicate and sodium sulfate, and the ratio of the two is 1:1; the pore regulating agent is composed of fatty alcohol polyoxyethylene ether and tributyl phosphate, and the ratio of the two is 2:3;
[0038] (3) weighing the auxiliary material and the cement powder base material prepared in (1) according to a mass ratio of base material to modifier of 99:1, and dry mixing and stirring, and after mixing evenly, the cement powder for sulfur-containing tailings can be obtained;
[0039] (4) Weighing 0.874 kg of the cement powder prepared in (2) above and mixing it with 7.494 kg of a sulfur-containing tailings mortar with a mass concentration of 70%, wherein the mass of the sulfur-containing tailings curing agent accounts for 14.3% of the dry weight of the sand in the sulfur-containing tailings mortar, that is, the cement-sand ratio is 1:6, adding 0.632 kg of water to adjust the mass concentration of the mixed slurry to 68%, and stirring evenly to obtain a sulfur-containing tailings cementitious filling material;
[0040] (5) The sulfur-containing tailings cementing filling material prepared in (3) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009).
[0041] Example 4
[0042] (1) 1.00 kg of sulfur-containing tailings cement powder is prepared according to the following mass ratio, wherein the cement powder is composed of a base material and auxiliary materials, wherein the mass percentage of the auxiliary materials in the cement powder is 1 wt%; the base material components of the cement powder are calculated by mass percentage, including: 77 wt% of slag powder, 3 wt% of silica fume, and 20 wt% of an active activator; the active activator includes silicate cement and desulfurized gypsum, wherein the mass ratio is 3:2;
[0043] (2) The modifier includes a solubilizer, an early strength agent, and a pore regulator, and the mass ratio thereof is 1:2:3; wherein the solubilizer is composed of sodium carbonate and calcium chloride, and the ratio of the two is 1:2; the early strength agent is a mixture of sodium fluorosilicate and potassium aluminum sulfate, and the ratio of the two is 1:1; the pore regulator is composed of fatty alcohol polyoxyethylene ether and tributyl phosphate, and the ratio of the two is 1:2;
[0044] (3) weighing the modifier and the cement powder base prepared in (2) according to a mass ratio of base material to modifier of 99:1, dry mixing and stirring, and obtaining cement powder for sulfur-containing tailings after mixing evenly;
[0045] (4) Weighing 0.788 kg of the cement powder prepared in (3) above and mixing it with 7.875 kg of a sulfur-containing tailings mortar with a mass concentration of 70%, wherein the mass of the sulfur-containing tailings curing agent accounts for 12.5% of the dry weight of the sand in the sulfur-containing tailings mortar, that is, the cement-sand ratio is 1:7, adding 0.338 kg of water to adjust the mass concentration of the mixed slurry to 70%, and stirring evenly to obtain a sulfur-containing tailings cementitious filling material;
[0046] (5) The sulfur-containing tailings cementing filling material prepared in (4) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009).
[0047] Example 5
[0048] (1) 1.00 kg of sulfur-containing tailings cementing material is prepared according to the following mass ratio, wherein the cementing powder is composed of a base material and auxiliary materials, wherein the mass percentage of the auxiliary materials in the cementing powder is 1 wt%; the base material components of the cementing powder are calculated by mass percentage, including: 77 wt% of slag powder, 3 wt% of silica fume, and 20 wt% of an active activator; the active activator includes silicate cement and desulfurized gypsum, wherein the mass ratio thereof is 3:2;
[0049] (2) The auxiliary materials include a dissolution promoter, an early strength agent, and a pore regulator, and the mass ratio thereof is 1:1:3; wherein the dissolution promoter is composed of sodium carbonate and calcium chloride, and the ratio of the two is 1:2; the early strength agent is a mixture of sodium fluorosilicate and potassium aluminum sulfate, and the ratio of the two is 1:1; the pore regulator is composed of fatty alcohol polyoxyethylene ether and tributyl phosphate, and the ratio of the two is 2:3;
[0050] (3) weighing the modifier and the cement powder base material prepared in (1) according to a mass ratio of base material to modifier of 988:12, and dry mixing and stirring, and after mixing evenly, a cement powder for sulfur-containing tailings can be obtained;
[0051] (4) Weigh 0.700 kg of the cement powder prepared in (3) above and mix it with 8.00 kg of sulfur-containing tailings mortar with a mass concentration of 70%, wherein the mass of the sulfur-containing tailings curing agent accounts for 11.1% of the dry weight of the sand in the sulfur-containing tailings mortar, that is, the cement-sand ratio is 1:8, add 0.300 kg of water to adjust the mass concentration of the mixed slurry to 70%, and stir evenly to obtain a sulfur-containing tailings cementing filling material;
[0052] (5) The sulfur-containing tailings cementing filling material prepared in (4) above is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009).
[0053] Comparative Example 1
[0054] (1) Weigh 0.900 kg of commercially available PO 42.5 cement and 7.714 kg of sulfur-containing tailings mortar with a mass concentration of 70%, wherein the mass of cement accounts for 14.3% of the dry weight of the sand in the sulfur-containing tailings mortar, that is, the mortar-sand ratio is 1:6, add 0.386 kg of water to adjust the mass concentration of the mixed slurry to 70%, and stir evenly to obtain a sulfur-containing tailings cementing filling material;
[0055] (2) The prepared sulfur-containing tailings cementing filling material is poured into a 7.07 mm × 7.07 mm × 7.07 mm triple ABS test mold, and then the test mold is placed in a standard curing box with a temperature of 20 ± 2 ° C and a relative humidity of 95%. After hardening, the mold is removed and the test block is continued to be placed in the standard curing box for curing. When the specified age is reached, the test block is taken out and the compressive strength test is carried out according to the "Standard for Test Methods for Basic Properties of Building Mortar" (JGJ / T70-2009). BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The following are the mechanical properties test results of different embodiments.
Claims
1. A cement powder for sulfur-containing tailings, characterized in that: The cement powder is composed of a base material and auxiliary materials. The base material of the cement powder includes the following raw material components by mass percentage: 60-90wt% slag powder, 1-5wt% silica fume, 35-9wt% active stimulant, and the sum of the percentages of each raw material is 100%.
2. The cementing powder for sulfur-containing tailings according to claim 1, characterized in that The specific surface area of the slag powder is ≥400m 2 / kg, the activity index at 7 days and 28 days was ≥70% and 95% respectively, and the Al2O3 content was >11%.
3. The cementing powder for sulfur-containing tailings according to claim 1, characterized in that The active activator raw material components are desulfurized gypsum and ordinary Portland cement clinker, and the mass ratio thereof is 1-20:5-40.
4. The cementing powder for sulfur-containing tailings according to claim 3, characterized in that The attached water content and chloride ion content of the desulfurized gypsum are ≤12% and 300 mg / kg respectively, and the content of calcium sulfate dihydrate (CaSO4·2H2O) is ≥90%.
5. The cementing powder for sulfur-containing tailings according to claim 3, characterized in that The specific surface area of the cement clinker is ≥300m 2 / kg, 28d flexural and compressive strengths are ≥6.5MPa and 42.5MPa respectively.
6. The cementing powder for sulfur-containing tailings according to claim 1, characterized in that The adhesive powder auxiliary materials account for 0.5-3wt% of the adhesive powder mass percentage, including a dissolution promoter, an early strength agent, and a pore regulator; further, the mass ratio of each raw material in the adhesive powder auxiliary materials is as follows: dissolution promoter: early strength agent: pore regulator is 20-40: 20-40: 20-60.
7. The cementing powder for sulfur-containing tailings according to claim 6, characterized in that The dissolution promoter is a combination of one or more of sodium carbonate, calcium chloride, and calcium nitrate; the early strength agent is a combination of one or more of sodium fluorosilicate, sodium sulfate, and potassium aluminum sulfate; and the pore regulator is a combination of one or more of fatty alcohol polyoxyethylene ether, tributyl phosphate, and polyether silicone.
8. The cementing powder for sulfur-containing tailings according to claim 1, characterized in that The sulfur content in the chemical composition of the sulfur-containing tailings is 5-15%, and the sulfur element mainly exists in the form of pyrite (FeS2).
9. A method for preparing a cement powder for sulfur-containing tailings, characterized in that: (1) weighing slag powder, silica fume, desulfurized gypsum and cement clinker according to a certain mass ratio, mixing, stirring and grinding to obtain a sulfur-containing tailings glue solid powder base material; (2) mixing and stirring the solvent promoter, early strength agent and pore regulator in the modifier in a certain mass ratio to obtain a sulfur-containing tailings glue solid powder auxiliary material; (3) The cement powder base material in (1) and the cement powder auxiliary material in (2) are mixed evenly to obtain the cement powder for sulfur-containing tailings.